“Adverbial” Anaphora Resistance in Students’ Descriptive Texts - Azis Azis; Juanda Juanda (Bina Nusantara University, 2020)
The research aimed to analyze adverbial anaphora resistance in students’ descriptive texts at the Department of Indonesian Language Education and Literature, Faculty of Languages and Literature, Universitas Negeri Makassar. The problem “How is adverbial anaphora (resistance) was presented in the descriptive texts written by the students? A descriptive qualitative content analysis was employed in the research. Data collection was performed through documentation of the five-semester students’ descriptive texts. The results show that adverbial anaphora resistance in the students’ descriptive texts consists of: (1) anaphora within adverbs of place (ini “this” and di sana “there” that occupy a different position); (2) anaphora within adverbs of time (tahun “year”, pagi hari “in the morning”, and malam hari “at night”); (2) anaphora within adverbs of purpose (bagi “for” and untuk “to”); (4) anaphora within adverbs of comparison (seperti “like”); (5) anaphora within adverbs of cause (sebab “cause” and karena “because”). Adverbial anaphora is highly associated with the placement of words, the relationship between words and phrases, or interrelationship among sentences. The limited number of adverbial anaphora produced by the students originates from the students’ lack of competence in writing a text.